Host immunity in the protective response to nasal immunization with a pneumococcal antigen associated to live and heat-killed Lactobacillus casei - Vintiñi, Elisa Ofelia (2011)
Background: At present, available pneumococcal vaccines have failed to eradicate infections caused by S. pneumoniae. Search for effective vaccine continues and some serotype independent pneumococcal proteins are considered as candidates for the design of new vaccines, especially a mucosal vaccine, since pneumococci enter the body through mucosal surfaces. Selection of the appropriate adjuvant is important for mucosal vaccines, and lactic acid bacteria (LAB) with immunostimulant properties are promissory candidates. In this work, we assessed the adjuvant effect of a probiotic strain, Lactobacillus casei (L. casei), when nasally administered with a pneumococcal antigen (pneumococcal protective protein A: PppA) for the prevention of pneumococcal infection. Adjuvanticity of both live (LcV) and heat-killed (LcM) was evaluated and humoral and cellular antigen-specific immune response was assessed in mucosal and systemic compartments. The potential mechanisms induced by nasal immunization were discussed.Results: Nasal immunization of young mice with PppA+LcV and PppA+LcM induced anti-PppA IgA and IgG antibodies in mucosal and systemic compartments and levels of these specific antibodies remained high even at day 45 after the 3rd Immunization (3rd I). These results were correlated with IL-4 induction by the mixture of antigen plus LcV and LcM. Also, PppA+Lc (V and M) induced stimulation of Th1 and Th17 cells involved in the defence against pneumococci. The protection against pneumococcal respiratory challenge at day 30 after the 3rd I showed that PppA+LcV and PppA+LcM immunizations significantly reduced pathogen counts in nasal lavages while prventing their passage into lung and blood. Survival of mice immunized with the co-application of PppA plus LcV and LcM was significantly higher than in mice immunized with PppA alone and control mice when intraperitoneal challenge was performed. No significant differences between the treatments involving LcV and LcM were found.Conclusions: Live and heat-killed L. casei enhanced the antigen-specific immune response when administered nasally with a pneumococcal antigen. Considering the potential risk associated with live bacteria, the design of a nasal vaccine based on pneumococcal antigens and heat-killed L. casei emerges as a safe and effective strategy for the prevention of pneumococcal infections and opens new possibilities of application of dead LAB as adjuvants in vaccine formulations against other pathogens.